Analisis Kinerja Lalu Lintas di Ruas Jalan Pemuda Kabupaten Kolaka - Lakawa, Irwan; Syamsuddin, Syamsuddin; Harisman, Harisman (Sultra Civil Engineering Journal (SCiEJ), 2024)
The purpose of this research is to determine the magnitude of the traffic flow that passes along the Jalan Pemuda Kolaka Regency section and determine the performance of the road as well as analyzing the operational performance of traffic on the Jalan Pemuda Kolaka Regency section including: capacity, degree of saturation (DJ), speed and travel time, level of service and knowing the condition of side obstacles on the Jalan Pemuda Kolaka Regency section. The data collection method is a direct survey by recording traffic volume and side obstacles. The research results obtained were the traffic volume at the observation point on the Jalan Pemuda Kolaka Regency section (direction Kolaka-Kolaka Utara) based on traffic volume values that the highest traffic activity occurred on Monday at 731 skr/hour at 16.00 – 17.00 and the lowest traffic activity occurred on Jalan Pemuda Kolaka Regency (North Kolaka-Kolaka direction), namely on Saturday at 316 skr/hour at 08.00 – 09.00. The peak degree of saturation on the Jalan Pemuda Kolaka Regency section (direction Kolaka-North Kolaka) is Monday at 07.00-08.00 with a degree of saturation of 0.50 and the Jalan Pemuda Kolaka Regency section (direction North Kolaka-Kolaka) is Monday 07.00-08.00 with a degree of saturation of 0.32. Side obstacles on the Pemuda Kolaka Regency road show the highest side resistance values occurring in the morning at 07.00 – 08.00 with a value of 629. For the side obstacle class on Jalan Pemuda Kolaka Regency for the total in both directions, namely T (high).